Impact of COVID-19 Fear on the Mental Health of Medical professionals: Gender Differences and Mental Health Outcomes - Aslam, Adeela; Tahira, Anum; Khalid, Muhammad (Annals of Human and Social Sciences, 2024)
The study investigated how COVID-19 fear impacts the mental health of medical professionals, with a focus on gender differences. Conducted as a cross-sectional survey among 300 medical professionals in Sargodha hospitals, findings revealed that COVID-19 fear significantly and negatively affected mental health outcomes. The study utilized a convenience sampling method and collected data using three self-report measures: the Fear of COVID-19 Scale (Ahorsu et al., 2020) and the Positive Mental Health Scale (Lukat et al., 2016). Regression analysis underscored that fear of COVID-19 was a predictor of poorer mental well-being. Significant differences in fear levels and mental health were noted between male (72.4%) and female (27.6%) participants. To enhance the reliability of results, future studies were recommended to increase sample sizes for greater representativeness and more robust conclusions. Additionally, the study highlighted the need for further research to address remaining gaps and deepen understanding of how COVID-19 fear impacts the mental health of medical professionals.